LOS ESTEREOTIPOS Y LOS PREJUICIOS: CAMBIOS DE ACTITUD EN EL AULA DE L2 - Casal Madinabeitia, Sonia (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Student interaction in groups enriches the learning environment in the foreign language classroom. However, the risks of working in groups, such as the creation of stereotypes and prejudices, must be also pinpointed. According to the social identity theory, human beings need to classify individuals into categories or groups in order to make their world more understandable, believing (for no reason) that the group they belong to is superior to others. The classroom reflects this natural human tendency and groups are created around academic, social and peer evaluation criteria. Positive interdependence is presented as a tool to create a social situation where students need one another to succeed, modifying students’ attitudes towards other groups and promoting the positive side of working in groups.